What to expect of the first ERS/ECFS Adult Cystic Fibrosis Conference - Kisseleff, Jenai (2023)
This article provides a brief overview of the Adult Cystic Fibrosis Conference (#ACFMilan2023) programme, which will be held on 1–2 December 2023, in Milan (Italy) and online.